2014
DOI: 10.1007/s11764-013-0338-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of newly diagnosed comorbidities among breast cancer survivors

Abstract: Reducing overweight and regular sport/cycling activities may help to prevent CVD after breast cancer. Patients should be monitored for risk factors and advised on possible cardiac side effects of AI and trastuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
0
23
2
Order By: Relevance
“…The explanation underlying the increased risk of cancer in stroke survivors in all age groups is not fully known. A relatively high prevalence of preexisting or incident cardiovascular disease and risk factors has been recognized in patients with cancer [18,19,20,21]. There may not be a cause-and-effect relationship between the two disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation underlying the increased risk of cancer in stroke survivors in all age groups is not fully known. A relatively high prevalence of preexisting or incident cardiovascular disease and risk factors has been recognized in patients with cancer [18,19,20,21]. There may not be a cause-and-effect relationship between the two disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor is the combination of glucocorticoids and antiemetics used to minimize the side effects of CTx agents 8,11 . Psychological stress-related emotional volatility and start of menopause may also be related to weight gain during CTx 12 . Interruption of ovarian function reduces metabolism, muscle mass, and energy expended, and also stimulates fat accumulation [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease risk was often conceptually defined as incidence of cardiovascular diseases including ischemic heart disease, congestive heart failure, myocardial infarction, coronary artery disease, stroke, angina, atrial fibrillation, paroxysmal tachycardia, nonrheumatic valve disease, cardiomyopathy, aortic aneurysm, and arteriosclerosis. [3][4]8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] While one study included angina as a cardiovascular disease risk factor, 15 Darby et al indicated that angina would not be included as a risk factor due to difficulty with clinical identification of angina. 19 Other investigators conceptually defined cardiovascular disease risk as the presence of cardiovascular disease risk factors including smoking and having an overweight or obese body mass index.…”
Section: Conceptual Definitionsmentioning
confidence: 99%
“…3,[32][33][34][35][36][37][38][39][40] Four studies used self-reported history of cardiovascular diseases or cardiovascular disease risk factors as an operational definition. 23,28,30,31 Attributes According to Rodgers, attributes provide a "real definition as opposed to a nominal or dictionary definition". 12 Attributes are the features that comprise the concept as opposed to the conceptual definition of the concept.…”
Section: Operational Definitionmentioning
confidence: 99%
See 1 more Smart Citation